Adult-capture assays as a tool to measure insecticide resistance in Anopheles malaria vectors: a modeling comparison with larval-capture assays - Holmdahl, Inga; Buckee, Caroline O.; Childs, Lauren M. (Frontiers in Malaria, 2025)
Systematic, long-term, and spatially representative monitoring of insecticide resistance in mosquito populations is urgently needed to quantify its impact on malaria transmission, and to combat failing interventions when resistance emerges. Resistance assays on wild-caught adult mosquitoes (known as adult-capture) offer an alternative to the current protocols, which recommend larval capture. Adult-capture assays can be done in a shorter time frame, in more locations, and in the absence of an insectary. However, unlike insectary-raised mosquitoes, a group of adults captured in the wild represents different ages and may have previous exposure to insecticides. Since age and prior exposure are critically important in determining the likelihood of death during the assay, taking these factors into account is important for assessing the relative utility of the assay. Currently such quantitative assessments are lacking. We developed a discrete-time deterministic model to simulate the mosquito life cycle, including insecticide exposure due to insecticide-treated bed nets. We incorporated non-lethal effects of insecticide exposure demonstrated in laboratory experiments and the impact of multiple exposure to insecticides on mosquito death rates during the assay. We then sampled from this population using both larval-captured and adult-captured mosquito collection and simulated insecticide resistance assays. To quantify possible biases in adult-capture assays, we compared the results of these assays to the true resistance allele frequency in the population. In simulated samples of 100 test mosquitoes, reflecting WHO-recommended sample sizes, we found that adult-capture samples had a 94% positive predictive value (PPV) for resistance at the WHO’s 10% resistance cutoff, and a 97% negative predictive value (NPV), compared to 98% PPV and 19% NPV for larval-captured samples. Bias in the adult-capture assays was primarily dependent on the level of insecticide resistance rather than coverage of bed nets or exposure heterogeneity. Using adult-captured mosquitoes for resistance assays may have advantages over larval-capture collection in many settings, and in our model does not appear to be significantly less accurate than larval-capture, especially when used to categorize resistance under the binary WHO criteria. These results suggest that adult-captured assays could be deployed for resistance monitoring programs at a more widespread scale.